Assessment of Training of Community Pharmacists towards the Prevention of COVID-19 in a North Central State of Nigeria - Olayinka Stephen Ilesanmi; Aanuoluwapo Afolabi; Oluwatosin Fakayode; Stephen Arigidi; Barakat Olatayo Olanrewaju (Research Center for Rational Use of Drugs (RCRUD), 2020)
Background: Community pharmacists(CPs) are key providers of basic healthcare in communities, and barriers that may hinder enormous results in their role during the COVID-19 pandemic should be addressed. We conducted training on the strategies for strengthening the Infection Prevention and Control (IPC)among CPs. Methods: Participants were 31 CPs in Ilorin, Kwara State. A quasi-experimental, before-and-after study was carried out. Data were captured using a self-administered questionnaire. The questionnaire had three sections; the frst contained sociodemographic characteristics such as sex, age, and years of practice. The second section contained eight questions used to assess the knowledge of the respondents, each was assigned a score of "1" and the total obtainable score was "8". The third section identifed the role of CPs in the prevention of COVID-19. Results: The mean age of the 31 CPs who participated in the training was 49.5 ± 13.7 years, and18 (58.1%) were males. The mean pre-test IPC training score was 4.968±1.329, while the meanpost-test IPC training score was 5.323±1.077, (t=-1.611, p=0.118). All respondents identifed that CPs had roles in the prevention of COVID-19. Among them, 27 (87.1%) identifed community health awareness campaigns as their main role in the prevention of COVID-19. Regarding years of practice, 6 (35.3%) respondents with less than 20 years had COVID-19 IPC knowledge gain compared to 10 (71.4%) others with more than 20 and above years of practice (P=0.04). Conclusion: The training achieved its short-term objective. There is a need to for supervisory visits on the CPs at their place of practice to ensure knowledge acquired is put to the best use.